Impact of tourism industry performances on tourist receipts:evidence from sri lanka after the liberalization of the economy - Gunarathne, G.S.P.; Perera, P.D.M.V. (University of Jaffna, 2018)
Most literatureprovides that tourism industry positively contributes to economic growth of developing countries. It is more important to identify the factors that effectfor the growth of tourism industry performances; tourist receipts. The general objective of this study is to estimate the contribution of factors affecting for tourist receipts in Sri Lanka. Existing literature suggests that tourist arrivals, excursionist arrivals, tourist nights, accommodation capacity & annual occupancy rate etc. are affected on tourist receipts. Time series analysis by using secondary data from 1977 to 2016employed to answer the research question. There is a long run relationship among all the variables. Among the factors, there is a significant positive impact of tourist arrivals & excursionist arrivals on tourist receipts in the short run although accommodation capacity, annual occupancy rate has asignificant negative impact. In addition, tourist nights does not indicate any significant short-run impact on tourist receipts. Hence, it can be concluded that there is a positive impact of tourist arrivals & excursionist arrivals on tourist receipts in Sri Lankan context. Therefore, this study strongly suggested taking appropriate policy actions to increase the tourist arrivals in order to acquire thehigher tourist receipts.
Keywords: Accommodation capacity; Excursionist arrivals; Tourist arrivals; Tourist receipts